2008
DOI: 10.1128/ec.00442-07
|View full text |Cite
|
Sign up to set email alerts
|

MPL1, a Novel Phosphatase with Leucine-Rich Repeats, Is Essential for Proper ERK2 Phosphorylation and Cell Motility

Abstract: The novel Dictyostelium phosphatase MPL1 contains six leucine-rich repeats at the amino-terminal end and a phosphatase domain at the carboxyl end. Similarly architectured phosphatases exist among other protozoa, such as Entamoeba histolytica, Leishmania major, and Trypanosoma cruzi. MPL1 was strongly induced after 5 h of development; ablation by homologous recombination led to defective streaming and aggregation during development. In addition, cyclic AMP (cAMP)-pulsed mpl1 ؊ cells showed reduced random and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…ErkB may control its own activity through feedback, as targets include the putative MAPK phosphatases MkpA and Mpl1 ( Rodriguez et al., 2008 ), which are phosphorylated in response to cAMP and folate, respectively. There may also be cross-talk between ErkA and ErkB, since phosphorylation of the activation loop of ErkA in cells depends on ErkB, and ErkB phosphorylates ErkA at a remote [S/T]PR site in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…ErkB may control its own activity through feedback, as targets include the putative MAPK phosphatases MkpA and Mpl1 ( Rodriguez et al., 2008 ), which are phosphorylated in response to cAMP and folate, respectively. There may also be cross-talk between ErkA and ErkB, since phosphorylation of the activation loop of ErkA in cells depends on ErkB, and ErkB phosphorylates ErkA at a remote [S/T]PR site in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…In the related parasite Leishmania , cAMP also appears to regulate stage transition 129 and motility 130 . Entamoeba , the causative agent of amebiasis, is another example of a parasite where cAMP-dependent pathways seem to regulate stage transition, in this case from the human intestinal form into the free-living cyst 131 .…”
Section: Camp Signaling In Parasitic Protozoamentioning
confidence: 99%
“…In particular, we found that macropinocytosis continues at a high rate in mutants of the PKA catalytic subunit, possibly accounting for the strong chemotactic defect of these strains (Scavello et al, 2017). Continued macropinocytosis could also confound studies on other strains with early developmental defects (Khosla et al, 2005;Wu et al, 1995;Rodriguez et al, 2008;Lee et al, 2005).…”
Section: Discussionmentioning
confidence: 89%